2019
DOI: 10.1587/transinf.2018mup0001
|View full text |Cite
|
Sign up to set email alerts
|

Image Manipulation Specifications on Social Networking Services for Encryption-then-Compression Systems

Abstract: Tatsuya CHUMAN †a) , Nonmember, Kenta IIDA †b) , Student Member, Warit SIRICHOTEDUMRONG †c) , Nonmember, and Hitoshi KIYA †d) , Fellow SUMMARY Encryption-then-Compression (EtC) systems have been proposed to securely transmit images through an untrusted channel provider. In this study, EtC systems were applied to social media like Twitter that carry out image manipulations. The block scrambling-based encryption schemes used in EtC systems were evaluated in terms of their robustness against image manipulation on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…We focus on EtC images which have been proposed for Encryption-then-Compression (EtC) systems with JPEG compression [2], [3], [6]- [9], [26]. EtC images not only have almost the same compression performance as that of unencrypted images, but also enough robustness against various ciphertext-only attacks including jigsaw puzzle solver attacks [9].…”
Section: Etc Imagementioning
confidence: 99%
See 2 more Smart Citations
“…We focus on EtC images which have been proposed for Encryption-then-Compression (EtC) systems with JPEG compression [2], [3], [6]- [9], [26]. EtC images not only have almost the same compression performance as that of unencrypted images, but also enough robustness against various ciphertext-only attacks including jigsaw puzzle solver attacks [9].…”
Section: Etc Imagementioning
confidence: 99%
“…Therefore, image compression is not applicable to these methods. As systems that satisfy both requirements 1 and 2, Encryption-then-Compression (EtC) systems have been developed [2], [3], [6]- [9], [26]. In this paper, we focus on a block-scrambling-based image encryption method that has been proposed for EtC systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New applications will be available over future Internet by using D2D communication and Internet connection. Social networking service (SNS) applications [10]- [13] are also available among neighboring users in D2D communication areas [14], [15]. In such D2D-based SNS, the data transmission over SNS can be performed with only D2D communications even when Internet connection is not available.…”
Section: Introductionmentioning
confidence: 99%
“…For privacy-preserving photo sharing on these services, three requirements need to be satisfied: 1) protection of visual information, 2) tolerance for recompression after encryption, and 3) identification of encrypted images. In terms of requirement 1, a lot of studies on secure and efficient communications have been reported [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. To secure multimedia data, full encryption with provable security, such as RSA and AES, is the most secure option.…”
Section: Introductionmentioning
confidence: 99%